David Franks : colonial merchant - Stern, Mark Abbott, 1929- (Pennsylvania State University Press, 2010)
"A biography of David Franks, an American Jewish merchant in Philadelphia during the colonial period and the War for Independence. A supplier to the British Army since the French and Indian War, Franks, though acquitted of treason, was forced out of Pennsylvania"--Provided by publisher